Designing and Developing Video as an Instructional Media in English Language Teaching Setting - Shalawati Shalawati; Missi Tri Astuti; Arini Nurul Hidayati; Sitti Hadijah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2022)
Using video in educational context has been established by many scholars as an effective instructional media to support the teaching and learning process. There have been numerous videos are available on social media platforms that can facilitate both teachers and students to easily access the videos as learning resources. However, the teachers are challenged to be able to provide their own learning resources, such as videos which are aimed to deliver the lessons in more contextual and authentic senses. In this regards, this study is aimed to encapsulate the design and development process of creating a video as an instructional media in English language teaching context. ADDIE (Analysis, Designing, Developing, Implementing, and Evaluating) framework was employed in the process of designing and developing the video. Documentation, observation, and testing were administered as data collection techniques to support the design and development of the video. Furthermore, this paper depicts the researchers’ experiences on the design and development of a video lesson as well as the survey findings. Implications of the findings for instructional design and recommendation for future research are also discussed.